DAMPAK GAME ONLINE ANTARA HIBURAN, EDUKASI, DAN KECANDUAN - Saputra, Suhanda; Ariadi, Fadly; Tiara Putri, Anggreita (PT Triputra Sejahtera Prima, 2025)
Online games have become a global phenomenon that influences various groups, especially the younger generation. On one hand, online games offer enjoyable entertainment and serve as a form of digital recreation; on the other hand, they also hold potential as interactive and engaging learning media. However, excessive and uncontrolled use of games can have negative impacts, particularly triggering addiction that may affect the mental health, social life, and academic performance of children and adolescents. This community service activity was carried out by a team of lecturers and students from Pamulang University at MTS Mathlaul Anwar, Pamulang, South Tangerang. The aim of this activity was to educate students about both the positive and negative impacts of online games, as well as to foster critical awareness in using digital technology wisely. The methods used included interactive lectures, open discussions, quizzes, and simulations of educational game usage. A participatory approach was also applied to actively involve participants in the learning process. The results showed that most participants initially perceived games merely as a form of entertainment. After the activity, their understanding broadened to include the potential risks of addiction as well as the educational value of games. Participants also showed interest in educational games and began to recognize the importance of time management in gaming. Through this program, students are expected to balance their digital activities and be able to choose games that are beneficial for personal development. This community service initiative makes a tangible contribution to building digital literacy and enhancing critical awareness among students regarding the use of entertainment-based technology. Future recommendations include the need for continued training involving parents and teachers in supervising and guiding the positive use of online